Junior High Robotics Inspiration: Engaging Students with Exciting Interactive Socialization - Agus Hayatal; Syamsudduha Syahrorini; Arief W; A.Arief DP; Dikas PN (Indonesian Journal of Cultural and Community Development, 2023)
This study elucidates the impact of a dynamic robot-focused socialization endeavor on the students of SMP Muhammadiyah 4 Porong. Targeting grades 7, 8, and 9, the initiative aimed to bridge the educational void resulting from the school's relocation. The presentation encompassed diverse national and international junior-level robot contests, along with rudimentary insights into robot components and their functionalities, aligning with the students' foundational aptitudes. Practical involvement, including hands-on interaction with an android smartphone-controlled sumo robot, generated enthusiasm reminiscent of play. A noteworthy upshot was the emergence of approximately 10 female students displaying a newfound interest in robotics. This venture not only augmented general knowledge but also spurred curiosity and engagement, emphasizing the potential for broader academic implications in the realm of junior high school education. Highlights: Interactive Exposure: The socialization event introduced students to national and international robot contests, fostering awareness and igniting interest in the field. Hands-on Experience: Through direct interaction with a smartphone-controlled sumo robot, students were engaged in a playful yet educational manner, encouraging active participation. Gender-Inclusive Impact: The initiative notably attracted around 10 female students, potentially contributing to gender diversity and inclusivity in the realm of robotics education. Keywords: Robotics, Junior High School, Socialization, Engagement, Sumo Robot